Respiratory Metabolism Responses of Chinese Mitten Crab, Eriocheir sinensis and Chinese Grass Shrimp, Palaemonetes sinensis, Subjected to Environmental Hypoxia Stress - Bao, Jie; Li, Xiaodong; Yu, Han; Jiang, Hongbo (Frontiers in Physiology, 2018)
Environmental hypoxia represents a major physiological challenge for Eriocheir sinensis and Palaemonetes sinensis and is a severe problem in aquaculture. Therefore, understanding the metabolic response mechanisms of E. sinensis and P. sinensis, which are economically important species, to environmental hypoxia and reoxygenation is essential. However, little is known about the intrinsic mechanisms by which E. sinensis and P. sinensis cope with environmental hypoxia at the metabolic level. Hypoxia–reoxygenation represents an important physiological challenge for their culture. In this study, respiratory metabolism and respiratory metabolic enzymes of E. sinensis and P. sinensis were evaluated after different hypoxia and reoxygenation times. The results showed that environmental hypoxia had a dramatic influence on the respiratory metabolism and activities of related enzymes. The oxygen consumption rates (OCR) significantly increased as hypoxia time increased, while the ammonia excretion rate (AER) was significantly lower than that in the control group after 8 h hypoxia. The oxygen to nitrogen ratio (O:N) in the control group was <16, indicating that all the energy substrates were proteins. After environmental hypoxia, the O:N significantly increased, and the energy substrate shifted from protein to a protein–lipid mixture. The OCR, AER, and O:N did not restore to initial levels after 2 h or 12 h reoxygenation and was still the same as after 8 h hypoxia. As environmental hypoxia time increased, succinate dehydrogenase (SDH) gradually decreased and lactate dehydrogenase (LDH) gradually increased. Both SDH and LDH were gradually restored to normal levels after reoxygenation. Therefore, environmental hypoxia should be avoided as much as possible during aquaculture breeding of E. sinensis and P. sinensis. Further, since OCR will significantly increase after a short period of reoxygenation, secondary environmental hypoxia due to rapid consumption of oxygen should also be avoided in aquaculture.